MODAL SOSIAL PADA PEDAGANG KAKI LIMA YANG TERGUSUR DARI KAWASAN FLY OVER PASAR PAGI ARENGKA KECAMATAN SIDOMULYO KOTA PEKANBARU - Kurnia Wahyuni; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study was conducted in Fly Over District pasarpagi in Sidomulyo Pekanbaru City. The purpose of this research is the social capital of street vendors who previously sold around the pasarpagi of the arengka. The focus topic of this research is knowing the barriers from the social capital of street vendors who previously sold around the morning market. The author uses qualitative methods and uses Sampling techniques purposive. Data instruments are observations, interviews and documentation. From the research conducted, the authors found that the research found that there were several social capital merchants who previously sold around the morning market of Arengka, namely the following: Trust, research finds the subject Research should start building new relationships with new customers. Give confidence to new customers who ask to be owed. This attitude is because the subject of research has missed many customers so have to re-find the new customer. Social networking, research finds, post-research subjects were displaced from the construction site of fly over Arengka, found the fact that research subjects should form a new social network especially with fellow traders. Values and norms, research finds the form of value and the norm that the subject of research is maintaining good relations with fellow PKL and assisting each other in trading.Research also finds that there are some obstacles from the social capital of merchants who previously sold around the morning market of Arengka, namely the following: difficult to acquire new customers, research finds that the subject of research difficulties Get new customers after being upset from a previous trading location. It is also due to the current trading location is less strategic. The trade location is not strategic, research finds the most fundamental economic change felt by research subjects especially due to the current trading location is not strategic. Keywords: Trust, Social Networking, Values and Norms